Low-kinetic energy impact response of auxetic and conventional open-cell polyurethane foams - Allen, T.; Shepherd, J.; Hewage, T. A. M.; Senior, T.; Foster, L.; Alderson, A. (Physica Status Solidi. B: Basic Solid State Physics, 2015)
This paper reports quasi‐static and low‐kinetic energy impact testing of auxetic and conventional open‐cell polyurethane foams. The auxetic foams were fabricated using the established thermo‐mechanical process originally developed by Lakes. Converted foams were subject to compression along each dimension to 85% and 70% of the unconverted dimension during the conversion process, corresponding to linear compression ratios of 0.85 and 0.7, respectively. The 0.7 linear compression ratio foams were confirmed to have a re‐entrant foam cell structure and to be auxetic. Impact tests were performed for kinetic energies up to 4 J using an instrumented drop rig and high speed video. A flat dropper was employed on isolated foams, and a hemispherical‐shaped dropper on foams covered with a rigid polypropylene outer shell layer. The flat dropper tests provide data on the rate dependency of the Poisson's ratio in these foam test specimens. The foam Poisson's ratios were found to be unaffected by the strain rate for the impact energies considered here. Acceleration‐time data are reported along with deformation images from the video footage. The auxetic samples displayed a six times reduction in peak acceleration, showing potential in impact protector devices such as shin or thigh protectors in sports equipment applications.